Contemporary left politics in South Africa: the case of the tri-partite alliance in the Eastern Cape - Hesjedal, Siv Helen (Rhodes University, Faculty of Humanities, Department of Sociology, 2010)
This thesis aims to make sense of Left politics in South Africa within the Tri-partite Alliance between the ANC, SACP and COSATU. The thesis focuses on developments in the Eastern Cape, between 2000 and 2008. The thesis describes the prevalent forms of Left politics in the Eastern Cape and the tendencies in the Alliance that organise this Left. The thesis also examines the historical, social and political conditions and that shape the form and content of Left politics in the province. Based on a survey of literature on what is considered the core manifestations of Left politics globally in the 20th Century Left politics is defined as the elements of the political spectrum that are concerned with the progressive resolution of involuntary disadvantage and with a goal of abolishing class society and capitalism. Although the Alliance as a whole should be seen to be on the Left on an international political spectrum, this thesis argues that the Left/Right dichotomy is useful for understanding the politics of the Alliance, as long as the second part of this definition is taken into consideration. The Alliance Left is understood as those leaders and activists within the Alliance that have the SACP and Cosatu as their operating base. It will be argued that this Left is, in its practice, largely concerned with what insiders refer to as politics of influence"Ÿ, rather than with politics of structural transformation"Ÿ. It is the ANC that is the leader of the Alliance and the party in government and thus it is on the terrain of ANC strategy, policy and positions that contestation in the Alliance plays itself out. Thus, for the Left, there is strength in the idea of the Alliance. However, there are significant theoretical and political weaknesses in the Left that undermine the possibility of making good use of various corporatist platforms to pursue the agenda of the Left in the Eastern Cape. There is also increased contestation within the Alliance Left itself about the continued usefulness of this strategy.
Keywords: Politics, Practical -- South Africa; Social classes -- South Africa -- History; Political parties -- South Africa; African National Congress -- South African; Communist Party; Cosatu; Eastern Cape (South Africa) -- Politics and government; Politics, Practical -- South Africa -- Eastern Cape